Saamelaiskulttuurin heikentämiskielto ja viranomaisten aktiivinen velvoite turvata perinteisten elinkeinojen harjoittamisen ja kehittämisen edellytykset - Heinämäki, Leena (Suomalainen Lakimiesyhdistys, 2025)
The prohibition to weaken Sámi culture and the obligation of the authorities to guarantee the conditions to practice and develop traditional Sámi livelihoodsThere are some 10,000 Sámi in Finland, members of the only indigenous people within the European Union. As an indigenous people, the Sámi have the constitutional right to practice and develop their language and culture. According to the Constitution, the Sámi also enjoy cultural and linguistic self-government in their home territory in Lapland. Sámi traditional livelihoods such as reindeer herding, fishing, and hunting are recognised as an integral part of their culture and thus constitutionally protected. There are several threats that Sámi livelihoods are facing, including, for instance, climate change, other competing land use and urbanisation. The aim of the article is to study the legal protection of Sámi traditional livelihoods with a particular focus on the “prohibition to weaken the Sámi culture”, a key concept recognised both in international and domestic legal settings. This includes a discussion of the overall legal status of the Sámi, including indigenous peoples’ right to self-determination and participation with the aim of their “free, prior, and informed consent”, which is a rather new concept in the international law concerning indigenous peoples. A further aim of this article is to point out challenges and difficulties that Finnish authorities have experienced when implementing the prohibition in their respective fields. The article shows that although e.g., the Mining Act and the environmental protection and water legislation in Finland recognise “the prohibition to weaken the Sámi culture”, which means a prohibition to cause “significant harm” to the Sámi culture and their rights as an indigenous people, the related cultural impact assessments, which would set a threshold for significance, are not being carried out in an adequate manner. Some public agencies, such as the Metsähallitus (the National Land Management Agency), do not consider ...